(untitled) (Fiep Bulletin - online, 2013)
Obesity is a disease that is increasing significantly and becoming common worldwide, affecting all social classes. It is defined as an excessive accumulation of fat mass. Pollock, Wilmore & Fox (1993) classified obesity into two, endogenous and exogenous. According to Bouchard (2003) observed an increase in sedentary lifestyle with decreased spontaneous search of physical activity and physical activity as both leisure and everyday. This fact demonstrates the importance of observing teachers in the attitudes of students, and to encourage those who have a life with enough daily physical activity, recreational or not. We analyze some physical education programs, which relate trends that have influenced them throughout their development until the present day. We approach issues about the acting of physical education in the pursuit of health through their classes and the benefits of pedagogical practice of physical education teacher in clarifying the consequences of obesity and associated diseases. The problem of the study was how the practice of teaching physical education teacher in the classroom helps to clarify the consequences of obesity in adolescent health? The justification was that obesity is related to many health problems and compromises the quality of life of adolescents. The aim of this study was to clarify the contribution of pedagogical practice of Physical Education Teacher in the development of knowledge about the causes and consequences of obesity in adolescent health. The methodology used is a literature search of the following keywords: obesity, adolescent and physical education. We consider such as Guedes (1999) that in the medical trends, through the military, biopsychosocial until sports, the physical education in health doesn’t have as aim to pursue its promotion effectively even in the present day.